(untitled) (Journal of Tourism and Himalayan Adventures, 2020)
The paper focuses on the sustainable and responsible tourism development in Nepal. It covers generally the historical tourism development and sustainable tourism perspectives with the example of influences in tourism sector through the infrastructural development in rural hilly and Himalaya areas. However, the development is directly related with the livelihood of communities; and the then issues of these communities should be addressed while planning and developing the particular areas; in some cases, the economic benefits come hand in hand with negative environmental and social impacts, these should be minutely examined and exercised to mitigate. Due to the manipulation and strong intervention, several regions have had to overcome disastrous environmental damage or the loss of their traditions and local culture in the infrastructural development that has directly impact on the growth of the tourism industry. In this regard, the paper has tried to provide some long-term economic operations practices, and the way to developing sustainable tourism development in Nepal on the base of the principles of sustainable tourism with pressures of commercialism of tourism sector. However, it is not the holistic approach for the sustainable development; and it has not covered all aspect of tourism development. Hence, further studies are required to address these all issues.